RANCANG BANGUN ALAT PENDETEKSI KETINGGIAN KOLOM CAIRAN INFUS MENGGUNAKAN SENSOR POTENSIOMETER DAN BERBASIS MIKROKONTROLER AT89S52 - Ayu Adi Susanti, Putu; Supardi, I Wayan; Suarbawa, K.N. (BULETIN FISIKA; Vol 17 No 2 (2016): BULETIN FISIKA, 2016)
It has been made a detector of the column height of the infusion fluid using by potensiometer sensor based on AT89S52 microcontroller. This detector was compiled by potensiometer, ADC0804, microcontroller AT89S52, seven segment, buzzer, and LED. The infusion fluid that used to calibrate the potensiometer sensor and the device’s working system was Otsu-NS infusion, while the infusion fluid that used to examine the device’s working system were aminovel infusion and NaCl infusion. The results of the present research were the device has conformity between system and aminovel infusion was 99.69% and 98.75% for NaCl that gained from linear regression analysis of device’s calibration data.